2013
DOI: 10.1039/c3cp52482e
|View full text |Cite
|
Sign up to set email alerts
|

Cu3MCh3 (M = Sb, Bi; Ch = S, Se) as candidate solar cell absorbers: insights from theory

Abstract: As the thin film photovoltaic sector continues to expand, there is an emerging need to base these technologies on abundant, low cost materials in place of the expensive, rare, or toxic elements such as Te, In, or Cd that currently constitute the industry standards. To this end, the geometric and electronic structure of four materials comprising low cost, earth abundant elements (Cu3SbS3, Cu3SbSe3, Cu3BiS3, and Cu3BiSe3) are investigated with the screened hybrid exchange-correlation functional HSE06 and their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 94 publications
10
61
0
Order By: Relevance
“…As a p‐type semiconductor with high absorption coefficient (over 10 5 cm −1 at visible wavelength), copper antimony sulfide (CAS) contains environmental‐friendly and earth‐abundant elements, and four major phases exist in the Cu‐Sb‐S system with a bulk bandgap range from 1.0 to 1.8 eV . Recently, several groups have demonstrated that CAS was a theoretically sustainable material for semiconductor‐based device applications . For example, Tablero analyzed the electronic properties of O‐doped Cu 3 SbS 3 , estimated the potential of this compound for photovoltaic applications .…”
Section: Introductionsupporting
confidence: 81%
“…As a p‐type semiconductor with high absorption coefficient (over 10 5 cm −1 at visible wavelength), copper antimony sulfide (CAS) contains environmental‐friendly and earth‐abundant elements, and four major phases exist in the Cu‐Sb‐S system with a bulk bandgap range from 1.0 to 1.8 eV . Recently, several groups have demonstrated that CAS was a theoretically sustainable material for semiconductor‐based device applications . For example, Tablero analyzed the electronic properties of O‐doped Cu 3 SbS 3 , estimated the potential of this compound for photovoltaic applications .…”
Section: Introductionsupporting
confidence: 81%
“…In another report, Cu3SbS3 thin films prepared by chalcogenization of Cu-Sb precursors have been reported with an optical band gap of 1.84 eV [27]. In a theoretical study, direct band gap energy of the Cu3SbS3 thin films was reported to be 2.14 eV [28]. Although the reported studies point to the appropriateness of the Cu3SbS3 for solar cell absorber layer, the disparity among different studies is obvious from the reported data.…”
Section: Introductionmentioning
confidence: 54%
“…Cu 3 SbS 3 with the wittichenite structure (P2 1 2 1 2 1 space group), has a computed HSE gap of 2.02 (indirect) and 2.14 (direct), and nanowires have been reported with an experimental optical gap of 2.95 eV. 311 This material has been doped with O S to raise the gap. A screening of antimony based thermoelectric sulfides computed Li 3 SbS 3 , Na 3 SbS 3 , and Ca 2 Sb 2 S 5 to have gaps of 2.96 eV, 3.14 eV and 2.11 eV, respectively, and low hole effective masses (not reported).…”
Section: A 2 B 3 Ch 4 and Dimensional Reductionmentioning
confidence: 99%